ANALISIS EFEKTIVITAS PENYALURAN DANA ZAKAT OLEH BAZNAS KABUPATEN LANGKAT TAHUN 2020 - Nabil Al Arif; Imsar Imsar (Universitas Muhammadiyah Prof Dr Hamka, 2022)
The authority locale government office responsible for gathering, circulating, and using zakat in all districts is the National Amil Zakat Agency (BAZNAS) which is settled in Langkat Regency. This study plans to look at the viability of the conveyance of zakat at BAZNAS in Langkat Regency in 2020. The subjective and quantitative strategies utilized in this study are portrayed in the accompanying segments. The subjective technique utilizes a graphic methodology. Rather than utilizing the Allocation to Collection Ratio (ACR) proportion estimation system in view of the Zakat Core Principles, a subjective methodology does as such (ZCP). To complete the examination, the 2020 Langkat Regency BAZNAS monetary report was utilized. The whole measure of ZIS gathered and appropriated during Langkat Regency in 2020 was Rp. 1,489,093,289, as per the BAZNAS report. 73% (73%) of appropriation in 2020 will be compelling or fall into the Effective class as per ZCP in light of information assortment and conveyance. This puts the 2020 Allocation to Collection Ratio (ACR) somewhere in the range of 70 and 89 percent